Could the choice of patient versus proxy ratings for assessing quality of life in dementia affect resource allocation in health care? - Alwin, Jenny; Brodtkorb, Thor-Henrik (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
OBJECTIVE: The aim of this paper is to demonstrate how the choice of patient versus proxy ratings of patient health-related quality of life (HRQoL) in dementia, for use in cost-effectiveness analyses (CEAs), could potentially affect resource allocation in health care.METHODS:A model of Alzheimer’s disease (AD) based on cognitive ability was used to assess the consequences of using HRQoL ratings from either patients themselves or proxies if a new treatment was to be introduced. The model was based on previously published data on costs related to AD stages as well as HRQoL ratings from AD patients and from their caregivers as proxy raters.RESULTS:The results show that there can be large differences in the results of the CEAs depending on whether the ratings of patients’ HRQoL were made by the patients themselves or by the proxy. When patient self-ratings of HRQoL were used, the cost/quality-adjusted life year (QALY) gained was much higher as compared to the scenario when proxy ratings were used for the same analysis.CONCLUSIONS: The choice of patient self-ratings compared to proxy ratings of patients’ HRQoL can have a substantial effect on the results of CEAs. These differences in results may have an important impact on decision making and, ultimately, on resource allocation. In order to critically appraise the results of CEA studies in dementia we advise that both patient and proxy ratings are used in the CEA. To decide on methodology it is of great importance that focus is directed towards determining the most valid way to measure HRQoL in AD.